2021
DOI: 10.3389/fmolb.2021.686110
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Root Exudates in Recruiting Streptomyces Bacteria to the Arabidopsis thaliana Microbiome

Abstract: Streptomyces species are saprophytic soil bacteria that produce a diverse array of specialized metabolites, including half of all known antibiotics. They are also rhizobacteria and plant endophytes that can promote plant growth and protect against disease. Several studies have shown that streptomycetes are enriched in the rhizosphere and endosphere of the model plant Arabidopsis thaliana. Here, we set out to test the hypothesis that they are attracted to plant roots by root exudates, and specifically by the pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…On the contrary, binary plant-bacteria interactions (positive, neutral, negative) were better predictors of SynCom’s effects on plants. Using the 13 C DNA Stable Isotope Probing technique, Worsley et al [ 203 ] demonstrated that several Pseudomonadota genera incorporated 13 C from PRE components when Arabidopsis is grown on compost.…”
Section: Arabidopsis Features That Shape Its Microbial Communitiesmentioning
confidence: 99%
“…On the contrary, binary plant-bacteria interactions (positive, neutral, negative) were better predictors of SynCom’s effects on plants. Using the 13 C DNA Stable Isotope Probing technique, Worsley et al [ 203 ] demonstrated that several Pseudomonadota genera incorporated 13 C from PRE components when Arabidopsis is grown on compost.…”
Section: Arabidopsis Features That Shape Its Microbial Communitiesmentioning
confidence: 99%
“… Saleh et al (2020) reported that citric acid, a root exudate of Brachypodium distachyon , acting as a strong chemoattractant for PGP bacterial strains. The hypothesis of Streptomyces species being attracted by the root exudates was tested and confirmed by Worsley et al (2021) on the root exudates of Arabidopsis thaliana . The study demonstrated that phytohormone, salicylate, plays a specific role in this process.…”
Section: Plant Growth-promoting Endophytic Bacteria–host Plant: Inter...mentioning
confidence: 99%
“…Many of the biomarkers, including for Bacillus, Pseudomonas, Agrobacterium, Gemmatimonas, Enterobacter, Streptomyces, Devosia, Ensifer, Acinetobacter, Halomonas, Brevundimonas, Mesorhizobium, and Burkholderia, are known as beneficial microbes for plants, and these microbes may help to maintain plant hormone balance, control root development, facilitate nutrition acquisition, and prevent disease in the plant host [42,44,[51][52][53][54][55]. Several studies have reported that Streptomycetes are abundant inside of the roots of Arabidopsis thaliana [56] where they can have beneficial effects on growth [57] or protect plants against biotic and abiotic stressors [58,59].…”
Section: Root Compartment-specific Bacterial Biomarkers Varied With G...mentioning
confidence: 99%